Daya Simpan Daging Ayam Broiler Pada Berbagai Volume Perendaman Ekstrak Daun Jambu Biji Merah (Psidium guajava) Selama Penyimpanan Suhu Dingin - Sari, Salsabila Permata; Damat, Damat; Husna, Afifa (Universitas Muhammadiyah Malang, 2025)
Food preservation, especially meat, is one of the studies in food technology that continues to grow. Meat spoilage is usually caused by Staphylococcus aureus and Escherichia coli bacteria. Red guava leaves are one of the food ingredients that have antimicrobial activity including tannin and flavonoid antibacterial compounds, so they have potential as natural ingredients for food preservation. This study aims to determine the effect of soaking red guava leaf extract (Psidium guajava) on the physicochemical properties of broiler chicken meat in cold storage. The method used was an experimental method with 6 treatments, namely soaking broiler chicken meat in 0 ml extract volume (P0) without soaking, 4 ml volume (P1), 6 ml volume (P2), 8 ml volume (P3), 10 ml volume (P4) and 12 ml volume (P5) for 30 minutes and storage duration of 0 days, 4 days and 8 days which were then stored at cold temperature 0-5 ℃. The analysis parameters included pH, moisture content, weight loss, texture, total bacteria value, and appearance. The results showed that the best soaking of red guava leaves in the P2 treatment was 6 ml extract soaking with a pH value of 5.78%-5.86%, moisture content 73.57%-66.37%, weight loss 0%-32.61%, texture 40.78-55.60, total microbial count 0.8 x104-0.5 x104 and appearance that can maintain quality.